Evaluating the benefits of TNF-alfa inhibitor biosimilar competition on off-patent and on-patent drug markets: A Southern European analysis - Barcina Lacosta, Teresa; Vulto, Arnold G.; Huys, Isabelle; Simoens, Steven (Frontiers in Pharmacology, 2022)
Background: The level of competition achieved following biosimilars market availability varies by country, care setting and molecule. Hence, biosimilars contribution to attaining price reductions and extended access to treatments can also vary. Objective: The aim of this study is to capture market dynamics for tumor necrosis factor (TNF)-alpha inhibitors and competing molecules in Southern European markets (2011-2020), and to evaluate the benefits of the competition generated by the availability of biosimilars. Methods: This study is based on a literature review examining market characteristics for TNF-alfa inhibitors and competing immunomodulator molecules, and on the quantitative analysis of market data for these molecules in Italy, Portugal and Spain. Results: Following biosimilars availability in Italian, Portuguese and Spanish markets, there has been an expansion in the overall access to TNF-alfa inhibitor pharmaceuticals. Further, savings have been generated within the TNF-alfa inhibitors class even after the increased use of these molecules. However, the potential of infliximab, etanercept and adalimumab biosimilars to generate price competition outside of their own drug class appeared limited in the studied markets. Considering this limitation and that shifts towards on-patent and higher-cost therapies have occurred after TNF-alfa inhibitor biosimilars availability, the importance of investing in biosimilars development for still on-patent immunology biologics is emphasized. Conclusion: This study highlights the need for policies that do not only seek higher utilization of biosimilars, but that also support a sustainable market for these products. This is expected to foster the future development of biosimilar medicines.